"They Drew An Entire People After Them": Subjectivity and Arrested Decolonisation in Ousmane Sembène's Xala. Issue 4 (19th May 2022) - Jilani, Sarah
Abstract : Ousmane Sembène's 1975 film Xala, a searing satire about the post-independence Senegalese elite, has received wide scholarly attention for its critique of crony capitalism masquerading as African socialism. This essay seeks to examine how Xala approaches the under-studied question of subjectivity under these circumstances, seeking to trace the film's key concern with the effects of such neocolonial conditions upon the wider populace. Proposing that the central allegory of Sembène's film – the native elite as complicit against and/or unable to spearhead national decolonization – is not the final but the starting point of the analysis it offers of the relationship between subjectivity and arrested decolonization, this essay argues Xala centres land dispossession as the primary issue in post-independence Senegal, both because it sabotages the redistributive promise of independence, and because it strips people of the material moorings of their sujectivities. In three interconnected discussions of sartorial self-fashioning, the politics of La Francophonie, and the kinship networks broken by land theft, I propose that Xala is an exposé of how structures and subjectivities are inseparably bound under conditions of neocolonialism, with the futurity of national decolonization dependent on transforming both.